The changing language of modern English drama, 1945-2005 - Dorney, Kate, 1975- (Basingstoke [England] ; New York : Palgrave Macmillan, 2009)
"This book contains an account of language and drama between 1945 and 2005, synthesizing linguistic and dramatic knowledge in order to illuminate the ways in which anxieties and attitudes toward language manifest themselves in discourses on and around English theatre of the period, and how these anxieties and attitudes reflect back through the theatre of this period"--Provided by publisher.
-- Introduction -- Language, Communication and Ideology -- Fetishising Communication on Stage -- 1945-1955: The 'Dissociation of Sensibility' and 'the Jewelled Epigram' -- 1956-1964: Moribund and Vital; Demotic and Epic -- 1964-1975: Revolution On and Off Stage -- 1976-1989: Staging the Nation -- 1990-2000: Talk is Cheap -- Coda: Likelike-ese Since 2000 -- Notes -- Bibliography -- Index .
Includes bibliographical references (pages 226-247) and index.
Keywords: English drama -- 20th century -- History and criticism; Linguistics in literature; English language -- Great Britain -- Style; English language -- 20th century -- Style; Theater -- Great Britain -- History -- 20th century